2021
DOI: 10.3390/ijms22073394
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Acts Synergistically with a High-Fat Diet in the Development of a Proinflammatory and Potentially Proatherogenic Endothelial Cell Environment in an Experimental Model

Abstract: Classic atherosclerosis risk factors do not explain all cases of chronic heart disease. There is significant evidence that gut microbiota may influence the development of atherosclerosis. The widespread prevalence of chronic Helicobacter pylori (H. pylori, HP) infections suggests that HP can be the source of components that stimulate local and systemic inflammatory responses. Elevated production of reactive oxygen species during HP infection leads to cholesterol oxidation, which drives atherogenesis. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
(121 reference statements)
0
23
0
Order By: Relevance
“…In addition, the presence of soluble immune complexes containing H. pylori antigens in the sera of CHD patients might reflect the systemic effects of H. pylori infection that are related to an increased inflammatory response in the vascular endothelium [ 13 ]. It has been shown that Caviae porcellus infected experimentally with H. pylori had more severe peripheral arterial stiffness compared to those non-infected [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the presence of soluble immune complexes containing H. pylori antigens in the sera of CHD patients might reflect the systemic effects of H. pylori infection that are related to an increased inflammatory response in the vascular endothelium [ 13 ]. It has been shown that Caviae porcellus infected experimentally with H. pylori had more severe peripheral arterial stiffness compared to those non-infected [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using the cell cultures of the primary gastric epithelial cells and fibroblasts of these animals, it was revealed that an increased amount of ROS was followed by an elevated rate of apoptosis, an upregulation of both the local and systemic metalloproteinase (MMP)-9 concentrations, and diminished cell integrity [ 9 , 10 ]. Recently, Krupa et al (2021) [ 30 ] showed that vascular endothelial cells are sensitive to H. pylori antigenic signals, which may initiate apoptosis in conjunction with an upregulation of MMP-9 [ 7 ]. It is possible that during infection with H. pylori both ROS and MMP-9-driven apoptosis may be involved in atherogenesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoyt et al, using the model of cultured pulmonary artery endothelial cells, showed that collagen is a survival factor against LPS-induced apoptosis [58]. Recently, Krupa et al showed the increased collagen I response of vascular endothelial cells exposed to LPS H. pylori [59]. In this study, in the milieu of LPS H. pylori and IL-33, migration of cells did not exceed 40% confluence, which may suggest some interference between bacterial LPS and host IL-33 signaling.…”
Section: Influence Of Lps H Pylori On Il-33-driven Cell Migrationmentioning
confidence: 99%